(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In every nation, juvenile criminality is a grave offence that undermines the social order. Juvenile crimes are on the rise everywhere, and young people are becoming more and more involved in violent crimes. Similar patterns of a rise in the number of violent crimes perpetrated by minors are seen in India. It is a major issue for the country, and finding a solution will require considerable consideration. In response to these developments, the Indian judiciary and legal system have modified certain statutes relevant to juvenile justice in India. This research paper looks at the reasons for juvenile criminality and the solutions offered by academics in different professions to address the issue. According to a review of statistical data available on official websites, youth involvement in terrible crimes is on the rise. The Act related to Juvenile Criminality has been revised in order to address the issue of juvenile criminality in India. As a result, children accused of serious offences are now tried as adults.